Pendekatan Pembelajaran PKN MIS Fajar Shiddiq - Abdulgani Jamora Nasution; Rodiatul Hasanah Lubis; Annisa Rahimah Lubis; Siti Munawwaroh; Farhan Syaukani (Fakultas Tarbiyah IAI Nasional Laa Rooiba, 2023)
Citizenship Education (PKn) in elementary schools has an important meaning for students in the formation of private citizens who understand and are able to exercise their rights and obligations to become intelligent, skilled and characterized Indonesian citizens mandated in Pancasila and the 1945 Constitution. Learning is a process that is carried out by providing education and training to students to achieve learning outcomes. By using several approaches such as (1). Student-oriented or student-centered learning approach (student centered approach) and (2). Teacher-oriented or teacher-centered learning approach (teacher centered approach). Based on the explanation above, the title